PENGOMPOSAN SLUDGE HASIL PENGOLAHAN LIMBAH CAIR PT. INDOFOOD CBP DENGAN PENAMBAHAN LUMPUR AKTIF DAN EM4 DENGAN VARIASI SAMPAH DOMESTIK DAN BAWANG GORENG - Aisyah Azka Hidayati; Winardi Dwi Nugraha; Syafrudin Syafrudin (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
PT.Indofood an industry that produces liquid waste. The results form the side of the WWTP sludge that has not been managed well. This study used the results of WWTP sludge, domestic waste and waste from the fried onions PT.Indofood CBP as compost material. Aerobic compost processed within 50 liter plastic drum volume for 28 days with activators menambarkan EM4 and activated sludge. Comparison of sludge: domestic waste: used cooking onions row - helped the 6: 1: 1, 5: 2: 1, 4: 1.5: 1. The results showed that the mature compost variation with composition 6: 1: 1 is more optimal than the other variation with the ratio of C / N 12.99. The results of the majority of the variation in mature compost meets SNI 19-7030-2004, but to control the fried onions and domestic wastes do not meet these standards. EM4 compost activators have depreciation rate - the average is 59.44% greater than the activated sludge is 53.33%.